Paediatrics: how to manage scabies - Russell Thompson; Sean Westbury; Dana Slape (BioExcel Publishing Ltd, 2021)
This narrative review addresses scabies, a highly contagious, pruritic infestation of the skin caused by the mite Sarcoptes scabiei var hominis. Scabies is a common disorder that has a prevalence worldwide estimated to be between 200 and 300 million cases per year. Infestation is of greatest concern in children, the elderly, immunocompromised people and resource-poor endemic populations at risk of chronic complications. A diagnosis of scabies involves a clinical suspicion, a detailed targeted history, clinical examination and contact tracing. Dermoscopy and microscopy, where available, is confirmatory. Due to its infectivity and transmissibility, the management for scabies requires a multimodal approach: topical antiscabetic agents are the first line for most cases of childhood classic scabies and their contacts, which must also be identified and treated to prevent treatment failure and reacquisition. Environmental strategies to control fomite-related reinfestation are also recommended. Oral ivermectin, where available, is reserved for use in high-risk cases in children or in mass drug administration programmes in endemic communities. The prevention of downstream complications of scabies includes surveillance, early identification and prompt treatment for secondary bacterial infections, often superficial but can be serious and invasive with associated chronic morbidity and mortality. Post-scabetic itch and psychosocial stigma are typical sequelae of the scabies mite infestation. The early identification of patients with scabies and treatment of their contacts reduces community transmission. Although time consuming and labour intensive for caregivers, the implementation of appropriate treatment strategies usually results in prompt cure for the child and their contacts. Here, we provide a summary of treatments and recommendations for the management of paediatric scabies.